Hubungan Pelaksanaan Supervisi dengan Tingkat Kepatuhan Perawat dalam Pendokumentasian Asuhan Keperawatan di Ruang Rawat Inap RS Bhayangkara TK.II Jayapura - Fitri Nurani; Dyah Wiji Puspita Sari; Muh Abdurrouf (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Based on expert research, more than 50% of nurses do not comply with nursing care documentation. Incomplete documentation can result in hampered nursing care communication, which will negatively impact patient safety. Supervision by the head of the ward can be one of the factors that can influence the completeness of nursing documentation. This study was conducted with the aim of examining whether there is a relationship between the implementation of supervision and the level of compliance of a nurse in documenting nursing care in the inpatient ward of Bhayangkara Hospital Class II Jayapura. This study is a correlational analytical study with a cross-sectional design. The sample in this study amounted to 87 nurses in the inpatient ward of Bhayangkara Hospital Class II Jayapura from June - July 2025 obtained through a total sampling technique. Data were collected using a demographic questionnaire, a ward head supervision questionnaire, and an observation sheet for compliance with nursing documentation. The collected data will then be analyzed using the Spearman rank test. The results of the study showed that the implementation of supervision by the head of the room in the inpatient ward of Bhayangkara Hospital TK.II Jayapura was mostly in the sufficient category of 41 people (47.1%). Compliance with nursing documentation in the inpatient ward of Bhayangkara Hospital TK.II Jayapura was mostly in the compliant category of 52 people (59.8%). There was a relationship between the implementation of supervision and the level of nurse compliance in documenting nursing care (p value 0.000) and (r = 0.567). The results of this study will be input for the nursing service work unit so that evaluations can be carried out on nursing staff, work systems or facilities and infrastructure needed, such as efforts to maintain good supervision of the head of the room. In addition, it is expected that nurses can document immediately after the action, and record all actions taken completely.